PENGEMBANGAN BAHAN AJAR BAHASA ACEH UNTUK SISWA KELAS IV SEKOLAH DASAR DI NANGGROE ACEH DARUSSALAM - Ramli, Ramli (Jurnal Mentari, 2009)
The objective of this research is to develop the learning materials which are integrated of language skills: listening, speaking, reading, and writing, and the component of vocabulary and language structure. This research was carried out at the fourth year of the elementary school, ‘Sekolah Dasar Negeri 1’ Banda Aceh and ‘Sekolah Dasar Muhammadiyah 1’ Banda Aceh, Nanggroe Aceh Darussalam in September 2003 and from July to December 2007. Research methodology used is the research and development (R&D) by Dick and Carey. Instruments used to collect data were questionnaire, interview, and test. Then, the data analyzed qualitatively and quantitatively. The findings of the research are two units of learning materials which is each of it consist of four topics of materials. This research concludes that the product of the development of learning materials of Acehnese language is effective to be applied in elementry school.     DAFTAR PUSTAKA Anderson, Anne dan Tony Lynch. 1988. Listening. Oxford: Oxford         University Press. Bakhrum, T., dkk. 2002. Peulajaran Basa Aceh keu Murit Sikula Dasa. Medan: Penerbit PT Pabelan Medan. Borg, Walter R. and Meredith Damien Gall. 1983. Educational Research: An Introduction. New York: Longman. Byrne, Donn. 1998. Teaching Writing Skills. New Edition. London: Longman Group UK Limited. Cunningsworth, Alan. 1995. Choosing Your Coursebook. Cambridge: Cambridge University Press. Dick, Walter and Lou Carey. 1996. The Systematic Design of Instruction. Fourth Edition. New York: Longman. Dubin, Fraida and Elite Olshtain. 1986. Course Design: Developing Programs and Materials for Language Learning. Cambridge: Cambridge University Press. Funk, Wilfried dan Norman Lewis. 1971. Thirty Days to more Powerful Vocabulary New York: Pocket Books. Graves, Kathleen. 2000. Designing Language Course: A Guide for Teachers. Boston: Heinle & Heinle Publiher. Gumperz, John J. and Dell Hymes (ed.). 1972. Direction in Sociolinguistics, The Ethnography of Communication. USA: Holt, Reneharth and Wiston, Inc. Hardley, C. Alice Omaggio. 1986. Teaching Language in Context. Boston: Heilne & Heinle Publisher, Inc. Harris, A. J. 1967. Reading on Reading Instruction. New York: David McKay Company, Inc. Harmer, Jeremy. 2001. The Practice of English Language Teaching. Third Edition. London: Longman Group UK Limited. Lani, Razali Cut dan Muhammad. 2002. “Kurikulum Bahasa Aceh Madrasah Dasar/Madrasah Ibtidaiyah.” Banda Aceh: MPD Provinsi NAD. McDonough, Jo and Christopher Shaw. 1993. Materials and Methods in in ELT. Oxford: Blackwell Publishers. Paulston, C. B. dan  Mary Newton Brider. 1976. Teaching English as A Second Language Techniques and Procedure. Massachusett: Winthrop Publisher, Inc. Purwo, Bambang Kaswanti. 2000. Bangkitnya Kebhinnekaan Dunia Linguistik dan Pendidikan. Jakarta: Mega Media Abadi. Richards, Jack C. and Teodore S. Rodgers. (ed.). 1986. Approaches and Method in Language Teaching. Cambridge: Cambridge University Press. Rost, Michael. Listening in Action. 1991. London: Prentice Hall International  (UK) , Ltd. Savignon, S. J. 1983. Communicative Competence: Theory and Classroom Practice. Reading Massachusetts: Addison-Wesley Publishing Company, Inc. Shambaugh, Neal dan Susan G. Magliaro. 2006. Instructional Design: A Systematic Approach for Reflective Practice. USA: Pearson Education. Tomlinson, Brian. 2001. Materials Development in Language Teaching. Cambridge: Cambridge University Press. The British Council. 1980. Project in Materials Design. London: The British Council, Printing and Publishing Department. Widdowson, H. G. 1978. Teaching Language as Communication. Oxford: Oxford University Press. Wildan. 2002. Tata Bahasa Aceh: untuk Madrasah Dasar dan Madrasah Menengah. Banda Aceh: Geuci. Wilkin, D. A. 1976. Notional Syllabuses. A Taxonomy and Its Relevance to Foreign Language Curriculum Development. Oxford: Oxford University Press.